Psychosocial impacts on family’s victims of forced disappearance - Romero Saenz, Laura Camila (2022)
Introduction Forced disappearance has been one of the practices that has been implemented by the state and armed groups outside the law, in order to be able to disappear people, in order to sow terror in the most vulnerable social sectors in Colombia, generating psychosocial impacts on society. Objective Therefore, this article aims to account for the phenomenon of forced disappearance and the complex situation that family members of a disappeared loved one go through, taking into account that this fact has left indelible marks in history. Methodology This article of reflection not derived from research results, presents a critical analysis, taking into account previous experiences in the field with respect to forced disappearance. Conclusion The crime of forced disappearance has generated various psychosocial impacts in all areas of adjustment of the human being, which has implied that the survivors cannot carry out the planning and implementation of an individual and family life project, evidencing themselves Psychosocial impacts at the community level: stigmatization and re-victimization scenarios, at the family level: reassignment of roles, break in the life cycle, permanent psychological suffering and individual level: uncertainty, breakdown of life projects, psychological discomfort, among others.